A prospective study on the role of neoadjuvant chemoradiotherapy on surgical outcome in resectable oesophageal carcinoma - Deka, Hrishikesh; Das, Bhabesh Kumar; Paul, Rajiv; Majumdar, Supriyo (International Journal of Research in Medical Sciences, 2021)
Background: Initial results of the chemo-radiotherapy for oesophageal cancer followed by surgery study (CROSS) comparing neoadjuvant chemoradiotherapy (NACRT) plus surgery versus surgery alone in patients with squamous cell carcinoma and adenocarcinoma of the oesophagus or oesophagogastric junction showed a significant increase in 5-year overall survival in favour of the NACRT plus surgery group after a median of 45 months’ follow-up. In this study we will interpret the short-term results of NACRT on resectable, locally advanced oesophageal carcinoma. Methods: Patients with clinically resectable, locally advanced cancer of the oesophagus or oesophagogastric junction (clinical stage T1N1M0 or T2-3N0-1M0, according to the AJCC, 8th edition) were assigned to receive weekly administration of four cycles of NACRT (intravenous carboplatin [AUC 2 mg/mL per min] and intravenous paclitaxel [50 mg/m 2 of body-surface area] for 23 days) with concurrent radiotherapy (41·4 Gy, given in 23 fractions of 1·8 Gy on 5 days per week) followed by McKeown’s oesophagectomy from 01 January, 2020 to 31 May, 2021. Results: It was observed in our study that 38.46% patients had achieved a CPR after the administration of NACRT as per the CROSS-trial protocol which is comparable to PCR achieved in CROSS trial (29%). All the patients underwent an R0 resection during surgery (100%) which is comparable to CROSS trial (92%).12 Conclusions: In our study which had collected data over a period of 17 months we learnt that the administration of NACRT in locally advanced oesophageal cancer was effective in reducing the tumor burden and achieving a satisfactory CPR of 38.46%.